Implementasi Data Warehouse Menggunakan Pentaho BI di Hartaning House Homestay - Hartani, Made Rusdinda; Mahendra, Ida Bagus Made (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2021)
Hartaning House is one of the homestays in Ubud Gianyar that rents out homestay rooms to foreign and local tourists, but currently does not have a data-based system that facilitates business reports. This research aims to provide a proposed solution in the form of designing and implementing data related to room rental, to facilitate the determination of the promotion of equal distribution of all homestay rooms. The implementation will use an open source application, namely (Pentaho Business Intelligence) for making reports that are used to facilitate analysis. The data is made in a multi-dimensional design to facilitate the application of the data warehouse design and system designs that have been made.